The role of lasers in the treatment of peri-implant diseases: A review - Fahad Ali Alshehri (Saudi Dental Journal)
We reviewed the indexed literature regarding the efficacy of laser therapy in the treatment of peri-implantitis (PI). Databases were searched using combinations of the following keywords: peri-implantitis, bone loss, photodynamic therapy, laser, and light-activated disinfection. Titles and abstracts of publications from these search results were screened to determine which studies fulfilled the eligibility criteria. Full texts of relevant studies were read and independently assessed against the eligibility criteria. The resulting 28 studies described the role of lasers in the treatment of PI. The erbium:yttrium–aluminum-garnet laser can be used to sterilize implant surfaces without damaging them. Likewise, the carbon dioxide laser can disinfect implant surfaces and enhance the bone-to-implant contact around previously infected sites. Photodynamic therapy exhibits high target specificity and can destroy pathogens associated with the etiology of PI. Laser therapy can significantly reduce levels of clinical markers of peri-implant tissue inflammation (i.e., bleeding upon probing and clinical attachment loss) without jeopardizing the integrity of the implant or alveolar bone. In conclusion, laser therapy as an adjunct to conventional mechanical debridement therapy can be used effectively for the treatment of PI. Keywords: Peri-implant bone loss, Dental lasers, Peri-implantitis, Photodynamic therapy, Decontamination, Review